Instructional design principles for developing a courseware for low vision and hearing impairment / Abdulrauf Tosho, Ariffin Abdul Mutalib and Sobihatun Nur Abdul-Salam - Tosho, Abdulrauf; Abdul Mutalib, Ariffin; Abdul-Salam, Sobihatun Nur (2016)
Instructional based on coursewares' interface face serious usability problem due to ineffective design towards content delivery. With restrictions in the interface design for diverse users, the conventional teaching and learning approaches requires people with disability to struggle more compared to their non-disabled counterpart learners. Meanwhile, the pedagogical applications that are specifically designed for the universality are highly scarce. This could be seen when most of the existing content applications that available in the market are designed for particular target user. This study presents an ongoing project, with the main objective to develop an instructional interface design principles in an attempt to cater for the needs of low vision and hearing impairment learners in their learning activities; called Courseware for Low Vision and Hearing Impairment (C4LVHI). Thus, to achieve the main objectives, this study comes up with specific objectives, which are: to determine the appropriate instructional interface elements and design principles of courseware design for low vision and hearing impairment learning. This could be as guidance for the developer or anyone who intend to develop courseware for low vision and hearing impairment. The recommended future works is to investigate the user experience of using C4LVHI among the low vision and hearing impairment learners in Learning Centres. The target participant would be low vision, hearing impaired and non-impaired learners from tertiary level.